HUBUNGAN BEBAN KERJA DENGAN EFEKTIVITAS KERJA PADA APOTEKER DAN TENAGA TEKNIS KEFARMASIAN DI INSTALASI FARMASI RSUD X - Anisa Dwi Kurniawati; Puguh Ika Listyorini; Hesty Latifa Noor (Jurnal Ilmiah Multidisiplin Ilmu, 2025)
The Pharmacy Installation of RSUD X served 1,164,190 prescriptions with a total of 6,261,058 types of medications throughout 2024. This high prescription volume impacted waiting times, with the average waiting time for compounded medications reaching 75.71 minutes and for non-compounded medications reaching 38.84 minutes, both of which exceeded the expected service standardsA medication error rate of 0,1% indicates that a high workload may reduce the work effectiveness of pharmacists and pharmaceutical technical staff. This study aims to determine the relationship between workload and work effectiveness among pharmacists and pharmaceutical technical personnel. A quantitative method with a cross-sectional approach was used. The study involved 96 respondents selected through total sampling. Univariate analysis showed that 10.4% of respondents experienced a low workload, 57.3% a moderate workload, and 32.3% a high workload. Meanwhile, the respondents' work effectiveness was categorized as ineffective in 26%, moderately effective in 61.5%, and effective in 12.5%. The Spearman Rank correlation test showed a significant negative relationship between workload and work effectiveness (p < 0.01; r = -0.388) indicating that higher workload tends to lower work effectiveness. This study concludes that the majority of respondents had a moderate workload with moderate work effectiveness, and there is a significant negative relationship between two. Therefore, RSUD X needs to conduct regular workload evaluations, maintain work balance, and improve work effectiveness through training and optimization of supporting facilities